PENGARUH DEBT TO ASSET RATIO, CURRENT RATIO, TOTAL ASSET TURNOVER, DAN FIRM SIZE TERHADAP RETURN ON ASSET - Ayuningrum, Anggrainy Putri; Susilo, Dwi; Wisma, Shinta Riskiana (Komunitas Manajemen Kompetitif, 2025)
This research was conducted on manufacturing companies in the Property and Real Estate sector listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This research is based on the fact that companies in the Property and Real Estate sector are seen as having good prospects related to primary needs by the community. This provides opportunities and opportunities that are open to develop so that it can attract investors to make investments. The role of this sector can be used to see the improvement of the economy in a country. This study aims to find out whether Debt to Asset Ratio, Current Ratio, Total Asset TurnOver, and Firm Size have an influence on Return on Asset, either partially or simultaneously. The number of samples that have been used in this study is 93 companies. The sampling technique in this study uses the purposive sampling method, where the researcher selects samples based on the assessment of several characteristics or criteria that have been determined. Data analysis used SPSS Version 20 with test tools, namely Descriptive Statistical Test, Classical Assumption Test (Normality Test, Heteroscedasticity Test, Multicoloniality Test, and Autocorrelation Test), Multiple Linear Regression Test and Hypothesis Test (F Test and t Test). The results of the analysis of this study show that the Debt to Asset Ratio has a negative and significant effect on Return on Asset, the Current Ratio has a negative and insignificant effect on Return on Asset, Total Asset TurnOver and Firm Size have a positive and significant effect on Return on Asset.